The Effectiveness of E-Worksheet Use in the Elementary Social Studies Teaching Course to Enhance Self-Regulated Learning among Preservice Elementary School Teachers - Karimatus Saidah; Muhamad Basori (Universitas Nusantara PGRI Kediri, 2026)
This study aims to determine the effectiveness of using e-worksheets in elementary social studies courses to improve students’ self-regulated learning (SRL). SRL is an important ability that enables students to manage, control, and evaluate their own learning processes independently. The use of e-worksheets is considered a digital learning medium that can encourage active student engagement in the learning process while also fostering greater learning autonomy. This research employed a quantitative approach with a pre-experimental design. The study was conducted by implementing e-worksheets as a learning intervention in elementary social studies courses. Research data were collected by measuring students’ SRL abilities before and after the treatment. Furthermore, the data were analyzed using a paired sample t-test to identify differences in students’ SRL abilities before and after the implementation of e-worksheets. The findings revealed a significant difference in students’ SRL abilities before and after the use of e-worksheets, with a significance value of 0.028 (<0.05). These results indicate that the use of e-worksheets is effective in improving students’ self-regulated learning abilities in elementary social studies learning.